How to control the Tuberculosis and HIV/AIDS dual epidemic - Philip Ifesinachi Anochie; Augustine Ajogwu; Godwin Okeke Kalu; Mfon Itoro- Obong Akpan; Edwina Chinwe Onyeneke; Anthony Chidiebere Onyeozirila (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
This review contains the novel approaches and innovations on how to control the Tuberculosis and HIV/AIDS dual epidemics. AIDS kills more than 8000 people every day worldwide. More than 5000 people die from TB every day.  HIV-positive people can easily be screened for TB; if they are infected, they can be given prophylactic treatment to prevent development of the disease or curative drugs if they already have the disease. TB patients can be offered an HIV test; indeed, research shows that TB patients are more likely to accept HIV testing than the general population.  This means that TB programs can make a major contribution to identifying eligible candidates for ARV treatment.  Many people, including those living with HIV, do not know that TB is curable. This is a basic message and one thing that is failing to get through. We should know how to get the message to policy- makers and funders that more drugs are needed for both diseases. It is not "either/or', there is no point providing ARVs only for patients to die of TB for lack of TB resources. Similarly, TB efforts alone are insufficient. HIV/AIDS is dramatically fuelling the TB epidemic in sub-Saharan Africa, where up to 70% of TB patients are co-infected with HIV in some countries. For many years efforts to tackle TB and HIV have been largely separate, despite the overlapping epidemiology. Improved collaboration between TB and HIV/AIDS programs will lead to more effective control of TB among HIV- infected people and to significant public health gains.